Appropriate Criteria: Key to Effective Rubrics - Brookhart, Susan M. (Frontiers in Education, 2018)
True rubrics feature criteria appropriate to an assessment’s purpose, and they describe these criteria across a continuum of performance levels. The presence of both criteria and performance level descriptions distinguishes rubrics from other kinds of evaluation tools (e.g., checklists, rating scales). This paper reviewed studies of rubrics in higher education from 2005 to 2017. The types of rubrics studied in higher education to date have been mostly analytic (considering each criterion separately), descriptive rubrics, typically with four or five performance levels. Other types of rubrics have also been studied, and some studies called their assessment tool a “rubric” when in fact it was a rating scale. Further, for a few (7 out of 51) rubrics, performance level descriptions used rating-scale language or counted occurrences of elements instead of describing quality. Rubrics using this kind of language may be expected to be more useful for grading than for learning. Finally, no relationship was found between type or quality of rubric and study results. All studies described positive outcomes for rubric use.